Exploring medication adherence in racial/ethnic minorities - Chery, Joronia; Gualtieri, Lisa; Lee, Ian; Sheng, Grace; Singhal, Meera; Ramos, Sebastian Z. (Frontiers in Pharmacology, 2025)
Introduction: Medication adherence remains a persistent challenge, particularly among racial and ethnic minority populations who experience cultural, structural, and environmental barriers to consistent medication use. Although adherence has been widely examined, less is known about the everyday practices and experiences that shape medication-taking behaviors. This study sought to explore home medication management routines among adults from racial and ethnic minority groups, with an emphasis on perceived challenges and facilitators of adherence.Methods: Semi-structured interviews were conducted with 20 adults from racial and ethnic minority backgrounds who were taking prescription medications. Interview transcripts were analyzed thematically to identify patterns in medication routines and factors influencing adherence.Results: Participants described a range of behaviors that shaped day-to-day medication use. Facilitators included visual cues and anchoring medications to established daily routines, while disruptions in routine were a common source of missed doses. Nearly half of participants (45%) reported mentally retracing their steps later in the day to determine whether they had taken their medication. More than half (55%) described giving or receiving support from other household members. Family experiences and cultural beliefs, including mistrust of clinicians, reliance on herbal remedies, and a strong emphasis on self-care, emerged as additional influences on medication-related decisions.Discussion: Findings illustrate how behavioral cues, household dynamics, and cultural beliefs shape medication adherence among racial and ethnic minority patients. Although limited by the small sample size, this study highlights opportunities for developing culturally responsive, behaviorally informed interventions that better integrate medication-taking into patients’ daily lives. Future research should build on these insights to inform scalable strategies that address persistent disparities in adherence.